DISPARITAS PUTUSAN TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA OLEH ANAK DALAM PERSPEKTIF HAM - Novena, Elisabeth Adisty; Soeskandi, Hari (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Narcotics users can be classified in various ways, including as narcotics addicts or victims of narcotics addiction. Naltrexone users and abusers are defined as those who use or abuse narcotics to the point of becoming physically and psychologically dependent on the drugs they use. In accordance with Article 54 of the Narcotics Law, the following things occur: It is specifically stated that "narcotics addicts and victims of narcotics abuse are required to undergo medical rehabilitation and social rehabilitation" and this refers to the provisions of SEMA No. 4 of 2010. Based on the Decision of the District Court of Semarang Number 407/Pid.SUS/2016/PN.Smg, the author gives examples of narcotics abusers who were ordered to undergo rehabilitation for 6 (six) months. The research method that the author uses is a normative juridical method, namely by conducting secondary data sources, namely data that are directly related to the problem being studied, and which consists of a number of data obtained from library books, laws and regulations, and others. related to the implementation of drug abuse rehabilitation programs. Following up on the research findings, the authors came to the conclusion that the legal considerations are that drug abusers must undergo medical rehabilitation and social rehabilitation in addition to imprisonment. In order to reintegrate into society, one's character and morals must be examined. For drug addicts, social rehabilitation is the process of reintroducing them to society, so they don't repeat their actions. Social rehabilitation also aims to reintegrate addicts and/or drug abusers into society by restoring thought processes, emotions, and behavios that are indicators of change. They have normal personality traits and are able to interact with others in their social environment (in a rehabilitation environment).